A Reciprocal University: A Model For Arts, Justice, and Community - O'Leary, Cecilia Elizabeth (Social justice, 2002)
Part of a special issue on new pedagogies for social change. An interview with Richard Bains, director of the Music and Performance Arts Institute at California State University, Monterey Bay, (CSUMB) and Amalia Mesa-Bains, artist and cultural critic. Topics discussed include reciprocal learning; the development of the experimental arts education model, the Reciprocal University Arts Project; the communities surrounding CSUMB; the process of creating community partnerships; students in the project; the concept of cultural citizenship; how Bains's experiences in music influenced the building of the project; what they hope to accomplish; how they and the community partners decided on different programs; how the struggle for social justice is reflected in the project's work; the obstacles encountered; working with community partners in relation to gang violence; the “Looking In, Looking Out” project and other projects; and the lessons learned during the first three years of the Reciprocal University.